1983
DOI: 10.1103/physrevb.27.474
|View full text |Cite
|
Sign up to set email alerts
|

Double sine-Gordon chain

Abstract: The thermodynamic properties of the double sine-Gordon chain are studied both analytically and numerically. Particular attention is given to the regime in which there are two different kinks (small and large) on the chain. The shape and energy of kinks are found in the continuum approximation.Comparison is made with numerical determination of the kink energies. The free energy, entropy, etc. of the chain are found. They are dominated by the small kinks. To see evidence for the participation of the large kinks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 18 publications
4
74
0
Order By: Relevance
“…Now we show that soliton complexes exist in the dispersive double sine-Gordon equations. These equations describe a large variety of physical systems: ferro-and antiferromagnets, magneto-elastic systems, superfluid 3 He and others [13]. Besides they contain dispersive sine-Gordon equations as the limit cases.…”
Section: Dispersive Models and Soliton-complex Solutionsmentioning
confidence: 99%
“…Now we show that soliton complexes exist in the dispersive double sine-Gordon equations. These equations describe a large variety of physical systems: ferro-and antiferromagnets, magneto-elastic systems, superfluid 3 He and others [13]. Besides they contain dispersive sine-Gordon equations as the limit cases.…”
Section: Dispersive Models and Soliton-complex Solutionsmentioning
confidence: 99%
“…The double sine-Gordon potential (DSG) provides twokink solutions that can be used to model thick branes [7,[45][46][47][48][49]. Previous works have showed that splitting branes with internal structure, generated by two-kink defects, can foment the presence of resonant states [13][14][15].…”
Section: Double Sine-gordon Branementioning
confidence: 99%
“…(2.9) by examining the effective potential (2.10). We follow the idea described in [13], i.e., we find the minima of (2.10) since these determine the shape of the kink solutions of Eq. (2.1) (see [13] for further details).…”
Section: A Methods Of Averagingmentioning
confidence: 99%
“…We follow the idea described in [13], i.e., we find the minima of (2.10) since these determine the shape of the kink solutions of Eq. (2.1) (see [13] for further details). We assume that all the parameters are positive real numbers, i.e., α > 0, 1 > 0, 2 > 0, 3 > 0, and 1 > 2 .…”
Section: A Methods Of Averagingmentioning
confidence: 99%